Effect of cooking modes on quality and flavor characteristic in Clitocybe squamulose chicken soup - Lai, Jing; Wu, Ruiyun; Wang, Ji; Wang, Ying; Zhang, Xin; Zhou, Liyuan; Zhu, Yingchun (Frontiers in Nutrition, 2022)
The effects of cooking modes (cooking in stainless-steel pot (SS), ceramic pot (CP), and electrical ceramic stewpot (EC) with different stewing time) on chemical compositions, whiteness, 5'-nucleotides, fatty acids (FAs), sensory quality and flavour substances in chicken soup added Clitocybe squamulose (Pers.) Kumm (a natural edible fungus) were investigated. The results showed that CP chicken soup had higher soluble solid matter (5.83 g/100mL), total sugar (2.38 mg/mL), crude protein (7.58 g/100g), and 5'-nucleotides (325.53 mg/mL) than EC and SS chicken soups. 48 volatile flavour compounds, mainly aldehydes and alkanes, were found by gas chromatography-mass spectrometry (GC-MS), and the characteristic flavour substances were identified by Principal component analysis (PCA) and orthogonal partial least squares discrimination analysis (OPLS-DA). Hexanal, (E,E)-2,4-decadienal and 3-methyl-hexadecane were the most abundant differential volatile compounds in the CP chicken soup. Additionally, the results of sensory evaluation showed that the chicken soup cooked in CP had the higher values of aroma, taste, and overall acceptability. Our results indicate that CP mode might be the best option for cooking chicken soup. This study provides a new perspective in the improvement of the quality and flavour of chicken soup by using an appropriate cooking mode. Theoretical support for the use of various cooking modes is also discussed to improve the quality of chicken soup at home and in the industry.